ACADEMIC STRESS AND GRATITUDE TO PROMOTE STUDENT WELL-BEING - Wahyuni, Sri; Hitami, Munzir; Afandi, Muslim; Agustina, Hellya (Psikis : Jurnal Psikologi Islami, 2022)
Research in education is developing very rapidly and widely, not only examining the cognitive domain but also starting to develop into the affective domain, such as research on student well-being. This study aimed to examine the correlation between academic stress and gratitude with student well-being. The approach used in this research is correlational quantitative. The research scale is given offline and online using a google form. Respondents in this study were 602 students of Madrasah Aliyah Pekanbaru, Riau, Indonesia. The instruments used are the academic stress, gratitude and student well-being scale. The results of data analysis with multiple regression analysis showed that there was a significant relationship between academic stress and gratitude with student well-being (p-value < 0.001; r 0.655), meaning that the hypothesis is accepted, with the effective contribution of academic stress and gratitude simultaneously on student well-being by 42.9%. Academic stress were negatively and significantly associated with student well-being when the gratitude variable was controlled (p < 0.001; Beta -0.521), and gratitude were positively and significantly associated with student well-being when the academic stress variable was controlled (p < 0.001; Beta 0.302). Furthermore, in qualitative data, the researcher found that some students felt stressed with the workload from school because they did not understand the subject matter, communication with teachers was not fluent, anxious and sad, afraid to disappoint parents, and dizzy and frustrated in thinking about the subject matter. The researcher recommends that schools organize training that can reduce academic stress and increase student gratitude, so that student well-being can increase.